2015
DOI: 10.1111/pme.12894
|View full text |Cite
|
Sign up to set email alerts
|

Familial Contributions to Self-Reported Sleep and Pain in Female Twins

Abstract: Objective The relationship between sleep quality and pain has been studied in populations with chronic pain and non-clinical populations in experimental paradigms. Little is known about the familial contributions to this relationship. This study examines self-reported sleep quality and pain in a non-clinical sample and to explore familial (i.e., shared genetic and common family environment) confounding in those relationships. Design Cross-sectional. Subjects 99 community-based female twin pairs (N = 198) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The pleiotropic nature of genes implies that the PGS of chronic pain may also be associated with disturbed sleep and vice versa. The PGS association between chronic pain and sleep disturbance are consistent with phenotypic cross-sectional links and findings from previous twin studies which showed the relationship between sleep and pain to be confounded by shared genetic and environmental factors 9,10,50 .…”
Section: Discussionsupporting
confidence: 88%
“…The pleiotropic nature of genes implies that the PGS of chronic pain may also be associated with disturbed sleep and vice versa. The PGS association between chronic pain and sleep disturbance are consistent with phenotypic cross-sectional links and findings from previous twin studies which showed the relationship between sleep and pain to be confounded by shared genetic and environmental factors 9,10,50 .…”
Section: Discussionsupporting
confidence: 88%
“…Depending on the condition (i.e., back pain, fibromyalgia), estimates of heritability for chronic pain have ranged from 25–68% (29), and the heritability of depression has been estimated at 31%–42% (30). Furthermore, recent work has suggested genetic contribution to the relationship between chronic pain and sleep quality (31) but was not able to evaluate the extent of this relationship. Overlap in the genetic factors contributing to sleep quality and depression has also been demonstrated (32) suggesting a shared etiology between these two phenotypes.…”
Section: Introductionmentioning
confidence: 99%